Victims' rights and victims' wrongs: comparative liability in criminal law - Bergelson, Vera (Critical perspectives on crime and law, 2009)
Victim's conduct in criminal law and criminology -- Why criminal law needs a generic defense of comparative criminal liability? -- What happens to victim's rights in situations of consent, self-defense and provocation? -- The principle of conditionality of rights -- How long do victim's rights remain limited? -- The defense of comparative criminal liability